Molecular Characterization of Carbapenemase (Blakpc-2) Gene From Klebsiella Pneumoniae Involved in Urinary Tract Infection in Al-Najaf City - Flyyih, Najat Mohammed; Abd Ali, Alaa Hashim; Al-Rammah, Ameer Abood Karim (Medical Science Journal for Advance Research, 2024)
Background: The human gastrointestinal tract, eyes, respiratory system, and genitourinary tract are all home to K. pneumonia. KPCs, or Klebsiella pneumonia carbapenemases, are β-lactamase enzyme types that have the ability to hydrolyze β-lactam drugs. Because of many co-morbid diseases, immunological suppression, and critical sickness, this KPC-producing strain infection can be fatal. In this study K. pneumonia was isolated from urinary tract infected patients, Where seven clinical urine specimen obtained from patients has UTI were gathered from different diagnostic Al-Sajjad Hospital in Najaf province the KPC gene was amplified by PCR. In this present study, a particular primer derived from the antibiotic sensitivity (blaKPC-2) gene is used to screen the urine samples collected for Klebsiella pneumoniae stains utilizing culture techniques then sequence analysis of the blaKPC-2 gene was conducted in order to gain a fresh understanding of the genetic variations. It’s interesting to note that, while comparing our strains’ blaKPC-2 open reading frame to previously released sequences, we discovered 6 mutations. Therefore, of the seven samples analyzed, three exhibited a positive band. The purpose of the primer was to amplify the bacteria’s blaKPC-2 antibiotic sensitivity gene. Conclusion: In this work, we verified a PCR technique for blaKPC-2 gene identification that is quick, sensitive, and specific. Out of the seven samples analyzed, three exhibited a positive band. The purpose of the primer was to amplify the bacteria’s blaKPC-2 antibiotic sensitivity gene.